PAMÄŤ A MOZOG: BERGSONOV OMYL. - PETIT, JEAN-LUC (Filozofia, 2019)
This article is dedicated to the area at the interface of philosophy and neuroscience and it focuses on the critical examination of some of Bergson's ideas. Neuroscience in its effort to strengthen the role of body in relation to mental processes and especially memory, cannot avoid discussing Bergson, namely his classic work Matter and Memory, in which he leaves the research of habitual memory to psychologists, while privileging the "pure memory? that surpasses psychophysical and psychocerebral parallelism, since it does not need any material substrate or location in space. However, new research in neuroscience puts this thesis into doubt, even denying it. The author takes into account research both in neuro-science (especially A. Berthoz) and in phenomenology and refers to works in this field that prove that the individualization of events, the subject of "episodic memory?, on the contrary, is a matter of space - and admits that Bergson was wrong, albeit not entirely, as confirmed by recent discoveries about the neural bases of memory. Moreover, neuroscience has so far read Bergson selectively, so the author intends to return to him and examine in particular the hippocampal function in the light of the cited work.